Legitimacy or Accountability? Corporate Disclosure of Economic Inequality in Indonesia’s ESG Star Listed Companies - Farhani Kautsar Nugraha (Universitas Muhammadiyah Palembang, 2026)
This study investigates how Indonesian ESG Star companies disclose economic inequality in their sustainability reports. Using a qualitative approach, the study applies narrative analysis and thematic coding to sustainability reports published by eight companies across multiple sectors during the period 2022–2024. Disclosures were evaluated across four themes: distribution of economic benefits, employee welfare, wage inequality and ratios, and social justice narratives. Results show that most disclosures are symbolic and normative, aimed at maintaining legitimacy rather than promoting substantive accountability. Employee welfare is consistently addressed, while executive-to-worker pay ratios and structural inequalities are often omitted or superficially treated. Social justice narratives emphasize compliance over critical engagement with systemic disparities. This study contributes to social accounting literature by highlighting sustainability reporting as a narrative tool of corporate legitimation and underscores the need for regulators and standard setters to strengthen disclosure requirements related to income distribution and wage transparency in emerging economies.